Analysis of Students' Mathematical Communication Ability in SPLDV Materials in terms of Verbal Linguistic Intelligence - Indah Okta Widyawati; Vera Dewi Susanti; Titin Masfingatin (Jurnal Mercumatika : Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
The purpose of this research is to describe the analysis of students' mathematical communication skills in solving SPLDV material questions in terms of verbal linguistic intelligence. The research method used in this study is a qualitative method. The subjects in this study were 3 students with high, medium and low levels of verbal linguistic intelligence. The results of this research shows that the KVLT subject can fulfill all indicators of mathematical communication both written and verbal in solving SPLDV questions. KVLT subjects can write and explain orally mathematical ideas or ideas, write and explain understandings related to mathematical ideas, and are able to use terms, mathematical notations and their structures in presenting an idea and describing relationships and situation models. KVLS subjects meet the indicators of communication skills written mathematics in expressing ideas or ideas in writing but lacking in explaining orally. KVLS subjects did not meet the indicators of mathematical communication skills in understanding and evaluating mathematical ideas both orally and in writing. Subjects are also less able to use terms, mathematical notation and structures in presenting an idea and describing relationships and situation models. KVLR subjects do not meet the indicators of mathematical communication in expressing ideas or ideas in writing and orally. The subject of KVLR does not meet the indicators of mathematical communication skills in understanding and evaluating mathematical ideas both orally and in writing, on indicators of mathematical communication skills in using terms, mathematical notation and structures in presenting an idea, as well as describing relationships and situation models the subject cannot meet indicators of mathematical communication skills both written and oral.Keyword: Mathematical Communication Skil, Verbal-Linguistic Intelligence, SPLDV